A STUDY OF YOUTH AGRICULTURE ENTREPRENEURSHIP CHARACTERISTICS ACCORDING TO THE PHILOSOPHY OF SUFFICIENCY ECONOMY - Pacharadit, Saksake; Patphol, Marut; Jamjuree, Danulada (RMUTT Global Business and Economics Review, 2022)
This research aimed to study the characteristics of youth agriculture entrepreneurship according to the Philosophy of sufficiency economy and study conditions of the characteristics of youth agriculture entrepreneurship according to the Philosophy of sufficiency economy of agricultural science students. The data were collected using mixed methods which qualitative research methods were applied with document analysis and in-depth interviews with 10 key informants. The data was verified through a focus group of 10 experts. After that, quantitative research methods were applied with a sample group of 308 agricultural science students. The Index of Item Objective Congruence (IOC) and the Alpha-Coefficient Cronbach were used to verify a questionnaire. Data were analyzed using research techniques; content analysis, mean, and standard deviation. The finding of this research showed that the characteristics of youth agriculture entrepreneurship according to the Philosophy of sufficient economy were consisted of 4 characteristics which characteristics 1 was seeking business opportunities based on your abilities, characteristics 2 was agricultural management, characteristics 3 was creativity and applying modern innovations to develop agriculture, and characteristics 4 was risk management and resilience based on the market situations. The results of the study of 4 characteristics condition of youth agriculture entrepreneurship of agricultural science students found that overall characteristics 1 of students in seeking business opportunities based on your abilities were high ( = 4.028 S.D. = 0.785) characteristics 2 of students in agricultural management was moderate ( = 2.834 S.D. = 0.774) characteristics 3 of students in creativity and applying modern innovations to develop agriculture were moderate ( = 2.964 S.D. = 0.752), and characteristics 4 of students in risk management and resilience based on the market situation were moderate ( = 2.988 S.D. = 0.744) respectively. This information was useful for higher education institutions in learning design, and extracurricular skills applied local wisdom developed students to have agricultural entrepreneurship characteristics that in line with the changing of an era.